Preparation, characterization, and in vivo evaluation of valsartan porous matrices using emulsion solvent evaporation technique - Babu, Govada Kishore; Babu, Puttagunta Srinivasa; Khagga, Mukkanti (International Journal of Pharmaceutical Investigation)
Introduction: Valsartan is a type II Biopharmaceutics Classification System (BCS) classified drug. The poor aqueous solubility restricts its use in developing sustained or controlled release systems for the treatment of chronic hypertensive conditions. The present investigation was conducted with an objective to formulate porous matrices (PMs) of valsartan in order to enhance aqueous solubility. Materials and Methods: Polyvinylpyrrolidone (PVP) K30 and poloxamer 407 were used as hydrophilic carriers; hexane was used as a pore-forming agent, ethanol was used as a solvent, and tween 20 was used as an emulgent. The prepared porous matrices were characterized and based on the maximum slope obtained from the Washburn method and other characterization results; the drug PVP K30 (1:1.5) was selected and further evaluated in vivo by the rat gut method. Results: The prepared porous matrices are white, free-flowing powders. Among prepared formulations drug PVP K30 (1:1.5) showed maximum Washburn slope of 0.0103. The mean particle size was found to be 0.82 µ and D50 (median) value was found to be 0.55 µ. The scanning of particles at various magnifications by scanning electron microscopy (SEM) analysis revealed that the method had effectively induced porosity. The Q value of valsartan from porous matrices was observed at 20 min with a first order regression value of 0.917. The calculated difference factor (F1) when compared with pure valsartan was observed to be 63.32%. From the values obtained, it was evident that the method amplifies the percentage of drug dissolution between sixfold and eightfold when compared to pure drug. From the absorption studies by the rat gut method, the absorption of porous matrices increased threefold. Conclusion: Porous matrices of valsartan: PVP K30 (1:1.5 ratio) hold promise for the enhancement of solubility and consecutive formulation of controlled release systems even with poorly soluble drugs.
Keywords: Hexane; poloxamer 407; porous matrices; polyvinylpyrrolidone (PVP) K30; valsartan; Washburn method